2021
DOI: 10.1007/s12144-021-02268-4
|View full text |Cite
|
Sign up to set email alerts
|

Do people have control over the decisions they make? Psychometric properties of the Italian version of the free will and scientific determinism questionnaire (FAD-plus-I)

Abstract: The FAD-Plus is a multidimensional measure of lay Beliefs in Free Will, Fatalistic Determinism, Scientific Determinism, and Unpredictability. This study had four aims: First, to test the factor structure of the Italian translation of the FAD-Plus in a sample of adults from the community, using structural equation modeling. Second, to test the reliability of the four scales. Third, to investigate gender invariance in item thresholds and factor loadings. Fourth, to analyze the criterion-related validity of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Some scholars have mentioned the impact of forestry infrastructure [17,18] on the development of forest tourism [19][20][21][22]. In addition, the effect of facilities for forest tourism on tourists' willingness to visit the urban forest park has been of interest, such as rock climbing [23], facilities such as maintaining access and parking for users [24] and other facilities in the forest park. Crilley et al [25] concluded that the benefits associated with a recreation experience can better affect the satisfaction of tourists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars have mentioned the impact of forestry infrastructure [17,18] on the development of forest tourism [19][20][21][22]. In addition, the effect of facilities for forest tourism on tourists' willingness to visit the urban forest park has been of interest, such as rock climbing [23], facilities such as maintaining access and parking for users [24] and other facilities in the forest park. Crilley et al [25] concluded that the benefits associated with a recreation experience can better affect the satisfaction of tourists.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing studies concluded that facilities for forest tourism are one of the factors affecting tourists' satisfaction and tourists' motivation [23][24][25][26][27]. However, few studies have systematically discussed how the facilities for forest tourism affect tourists' satisfaction.…”
Section: Introductionmentioning
confidence: 99%